2020
DOI: 10.1080/02670836.2019.1705587
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, phase evolution and corrosion behaviour of the Zn–Al–Mg–Sb alloy coating on steel

Abstract: In the present work, the influence of antimony (Sb) addition in Zn–Al–Mg alloy on the microstructure, phase characteristic, solidification behaviour and corrosion resistance of hot dipped Zn–0.5Al–0.5Mg– xSb ( x = 0, 0.1, 0.3 and 0.5 wt-%) coated steel wires were evaluated. Thermal analysis revealed that cooling rate of the liquid metal using the steel mould (5.3°C s–1) was higher than using ceramic mould (0.3°C s–1). Based on the phase analysis and verified by thermodynamic calculations, it was revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous studies have focused on the MgZn 2 phase within Zn-Al-Mg coatings, considered a crucial factor in enhancing these coatings’ corrosion resistance [ 3 , 12 , 13 ]. However, as research progresses, some studies have also identified the presence of the Mg 2 Zn 11 phase, indicating that the phase composition of these coatings is more complex than expected [ 8 , 14 , 15 , 16 , 17 ]. These findings have sparked the need for a deeper exploration of the phase transformation mechanisms occurring within these coatings, especially the transformation from MgZn 2 to Mg 2 Zn 11 and its specific impact on coating performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the MgZn 2 phase within Zn-Al-Mg coatings, considered a crucial factor in enhancing these coatings’ corrosion resistance [ 3 , 12 , 13 ]. However, as research progresses, some studies have also identified the presence of the Mg 2 Zn 11 phase, indicating that the phase composition of these coatings is more complex than expected [ 8 , 14 , 15 , 16 , 17 ]. These findings have sparked the need for a deeper exploration of the phase transformation mechanisms occurring within these coatings, especially the transformation from MgZn 2 to Mg 2 Zn 11 and its specific impact on coating performance.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of zinc-aluminummagnesium coating products mainly depends on the phase composition and microstructure, and the typical structures include a Zn-rich phase (a spherical and platy structure), a binary Zn/MgZn 2 eutectic phase (a coarse platy structure), and a ternary Zn/MgZn 2 /Al eutectic phase (a fine platy structure). Studies have shown that the MgZn 2 phase is the main reason for the improved corrosion resistance of a coating [9][10][11][12]. During the corrosion process, an electric couple is formed between Zn and MgZn 2 due to the potential difference between them.…”
Section: Introductionmentioning
confidence: 99%
“…As environmental conditions become increasingly complex, the requirements for corrosion-resistant Zn coatings are increasing and the galvanizing technology is gradually advancing toward the development of multi-alloy coatings. The corrosion resistance of Zn coatings was improved greatly by adding a certain proportion of Al and Mg [5][6][7]. Dense areas, such as Zn/Al/MgZn 2 ternary eutectic structures, were produced in the Zn-Al-Mg coating [8][9][10], which played a very important role during the corrosion process.…”
Section: Introductionmentioning
confidence: 99%